The intellectual capital of an enterprise: the innovative aspect - Miroshnychenko, Olga (Information & Media, 2013)
The interpretation of the category “intellectual capital” and approaches to determining the structure of intellectual capital have been considered in the study. The innovation capital, the use of which can increase the company’s competitiveness in the domestic and foreign markets, takes an important place in the structure of intellectual capital. The article contains analytical results of the innovation activity of Ukrainian enterprises. The prime factors limiting the innovation activity of Ukrainian enterprises have been defined. Consideration has been given to the features of financing innovation activities in Ukraine. The suggestions, the implementation of which at the state level shall promote the effectiveness of innovation activity of Ukrainian enterprises, have been put forward. Key words: intellectual capital, innovation, innovation activity, enterprise ИНТЕЛЛЕКТУАЛЬНЫЙ КАПИТАЛ ПРЕДПРИЯТИЯ: ИННОВАЦИОННЫЙ АСПЕКТ Oльга Mирошниченко Резюме В статье рассмотрена трактовка категории «интеллектуальный капитал», подходы к определению структуры интеллектуального капитала. Важное место в структуре интеллектуального капитала занимает инновационный капитал, использование которого способно повысить конкурентоспособность предприятия на внутреннем и внешнем рынках. Статья содержит результаты анализа инновационной активности украинских предприятий. Выделены основные факторы, ограничивающие инновационную активность предприятий Украины. Рассмотрены особенности финансирования инновационной деятельности в Украине. Внесены предложения, реализация которых на государственном уровне будет способствовать повышению эффективности инновационной деятельности украинских предприятий.